2009
DOI: 10.1016/j.healthplace.2008.07.004
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of First Nation and Inuit health: A critical population health approach

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited.In most cases authors are permitted to post their version of the article (e.g. in Word or Tex form) to their pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
298
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(312 citation statements)
references
References 34 publications
10
298
0
4
Order By: Relevance
“…Food in Nunavut, for example, on average costs twice as much in southern urban centres with household income significantly lower [45,59,60]. Ultimately, these causes can only be understood in the context of sweeping socio-economic transformations that have affected Inuit society over the last half century as former semi-nomadic hunting groups were resettled into permanent settlements beginning in the 1950s and incorporated into a colonial relationship with the Canadian state, detailed descriptions of which are provided elsewhere [12,17,61-63]. Iqaluit was one of the first permanently settled communities in the eastern Arctic, beginning with the building of a US Air Force base in 1942 [47,62,64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food in Nunavut, for example, on average costs twice as much in southern urban centres with household income significantly lower [45,59,60]. Ultimately, these causes can only be understood in the context of sweeping socio-economic transformations that have affected Inuit society over the last half century as former semi-nomadic hunting groups were resettled into permanent settlements beginning in the 1950s and incorporated into a colonial relationship with the Canadian state, detailed descriptions of which are provided elsewhere [12,17,61-63]. Iqaluit was one of the first permanently settled communities in the eastern Arctic, beginning with the building of a US Air Force base in 1942 [47,62,64].…”
Section: Discussionmentioning
confidence: 99%
“…Another consequence of these broader changes has been significant acculturative stress among northern populations, linked to the rapid changes in livelihoods and culture, and experience of residential schools [10,12,80-83]. Many of the older respondents were born and raised in small hunting camps, resettled in Iqaluit, spent time at tuberculosis sanatoria in southern Canada in the 1950s and 60s, and now live in a modern community.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies [44,45] demonstrate that the Mètis and Inuit population in Canada identified relationship with extended family members. Access to social resources and indigenous culture connections were identified as health determinants.…”
Section: Other Studiesmentioning
confidence: 99%
“…More common examples of their TF include moose, goose, ptarmigan, caribou and whitefish [3]. Not only do TF contribute nutritious, minimally processed food to the diet, but the harvesting and gathering activities involved in their procurement are also important to the health and well-being of Eeyouch , as they require physical activity and connect people to their traditional lands [4,5]. …”
Section: Introductionmentioning
confidence: 99%